2005
DOI: 10.1001/archinte.165.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Management in Patients With Coronary Artery Disease by a Clinical Pharmacy Service in a Group Model Health Maintenance Organization

Abstract: Background: Published data indicate that there is a significant treatment gap between the evidence for and the implementation of lipid-lowering therapy and that recidivism is as high as 60% at 1 year. The aim of this study is to examine the impact of a clinical pharmacy cardiac risk service (CPCRS) on lipid screening, control, and treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…Insurance products characterized as "others" are high deductible or triple option in our system; this association could reflect a particular patient-employer subset. At KPCO, antihyperlipidemic therapy is often instituted by a centralized pharmacist managed, physician monitored service, 32,33 and at primary care medical offices, clinical pharmacy specialists conduct lipid management. These services likely in part explain the association between prescribing by a non-primary care department and the antihyperlipidemic subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Insurance products characterized as "others" are high deductible or triple option in our system; this association could reflect a particular patient-employer subset. At KPCO, antihyperlipidemic therapy is often instituted by a centralized pharmacist managed, physician monitored service, 32,33 and at primary care medical offices, clinical pharmacy specialists conduct lipid management. These services likely in part explain the association between prescribing by a non-primary care department and the antihyperlipidemic subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies within the coronary artery disease population, males were more likely to be at goal. [23][24][25][26] Patients with diabetes were also more likely to attain goal. This finding may have been influenced by a KPCO initiative targeting statin initiation in patients with diabetes based on the results of the Heart Protection Study.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study, using a before-after design, evaluated the impact of a clinical pharmacy cardiac risk service on lipid screening, control, and treatment outcomes in more than 8,000 middle-aged and elderly male and female enrollees of a large group model health maintenance organization. The results of this study showed improvements in the outpatient management of LDL cholesterol levels as well as enhanced screening efforts for the identification of patients with elevated serum lipid levels [9]. …”
Section: Discussionmentioning
confidence: 99%